2016
DOI: 10.5585/rgss.v5i2.260
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho Econômico-Financeiro de Operadoras de Planos de Saúde Suplementar

Abstract: DESEMPENHO ECONÔMICO-FINANCEIRO DE OPERADORAS DE PLANOS DE SAÚDE SUPLEMENTAR RESUMO ECONOMIC AND FINANCIAL PERFORMANCE OF SUPPLEMENTARY HEALTH PLAN COMPANIES ABSTRACTThe federal regulation of the Brazilian sector of Supplementary Health has been stimulating competitiveness between companies specialised in this area, who seek a maximization of results, in addition to meeting the requirements of said regulation. In this context, the knowledge of the economic-financial performance becomes very important, since it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
1
2
0
3
Order By: Relevance
“…The analysis of the OPS indicators for the period under study indicates that the companies are well situated in economic-financial terms in comparison with the major banks, medium-sized banks, industry in general and the commerce and services sector (with the exception of health services) (IA, 2012). The results of the analysis are similar to those Silva & Loebel (2016) registered for the period 2008 to 2012 not only in terms of profitability but also in terms current liquidity, indicating consistent performance over time. In regard to variability, the indicators demonstrate a reasonable degree of homogeneity, in alignment with the result presented by Xavier & Souza (2020) based on information for the period 2010 to 2015.…”
Section: Discussion Of the Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…The analysis of the OPS indicators for the period under study indicates that the companies are well situated in economic-financial terms in comparison with the major banks, medium-sized banks, industry in general and the commerce and services sector (with the exception of health services) (IA, 2012). The results of the analysis are similar to those Silva & Loebel (2016) registered for the period 2008 to 2012 not only in terms of profitability but also in terms current liquidity, indicating consistent performance over time. In regard to variability, the indicators demonstrate a reasonable degree of homogeneity, in alignment with the result presented by Xavier & Souza (2020) based on information for the period 2010 to 2015.…”
Section: Discussion Of the Resultssupporting
confidence: 77%
“…Generally speaking, the results are similar to those of other studies despite the differences in methodological procedures. As examples: using hierarchic models, Baldassare (2014) found performance differences in the aspects of returns, liquidity and sinistrality that were related to the nature and size of the operator and modality; with their variance analysis, Silva & Loebel (2016) found that year and operator size and region had a significant influence on economic-financial performance as shown by the indicators for profitability, liability, liquidity and sinistrality; using Data Envelopment Analysis, Xavier (2017) identified differences in economic-financial performance explained by modality, size, region, headquarters location, and seal of accreditation; and lastly, Silva et al (2021), by means of variance decomposition indicated that national or regional coverage and the OPS brand explain most of the differences in profitability.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…A sinistralidade média, calculada a partir da razão entre as despesas assistenciais e receitas provenientes das mensalidades, correspondeu a 82%, em 2015. Apesar de positivo, o índice de sinistralidade mostra que as OPS podem estar operando com um resultado crítico, na medida em que se recomenda que esse índice fique abaixo de 70%-75% (CASTRO NETI; DE OLIVEIRA, 2012;SILVA;LOEBEL, 2016). Quando consideradas as despesas administrativas e comerciais e as receitas financeiras no cálculo do índice de sinistralidade, o resultado para a média dessas operadoras é de 96%, implicando uma margem de lucro de apenas 4%.…”
Section: Discussionunclassified
“…A análise dos indicadores das OPS no período indica que as empresas se encontram bem posicionadas em termos econômico-financeiros quando comparadas a grandes bancos, médios bancos, indústria em geral e comércios e serviços, exceto serviços de saúde (IA, 2012). A análise também aponta similaridades com os resultados registrados por Silva & Loebel (2016) para o período de 2008 a 2012, tanto em termos de rentabilidade como em termos de liquidez corrente, indicando desempenho consistente no tempo. Em termos de variabilidade, os indicadores apontam razoável homogeneidade, resultado também destacado por Xavier & Souza (2020) a partir de informações para o período de 2010 a 2015.…”
Section: Discussão Dos Resultadosunclassified
“…Os resultados, em geral, encontram semelhança com outros estudos, ainda que para procedimentos metodológicos distintos. Por exemplo, Baldassare (2014) encontrou, por meio de modelos hierárquicos, diferenças de desempenho em retorno, liquidez e sinistralidade relacionadas à operadora, modalidade e porte; Silva & Loebel (2016) encontraram, a partir de análise de variância, influencias significativas do ano e do porte e da região da operadora no desempenho econômico-financeiro avaliado por indicadores de rentabilidade, endividamento, liquidez e sinistralidade; Xavier (2017), por meio de análise envoltória de dados, identificou diferenças de desempenho econômico-financeiro de operadoras explicadas por modalidade, porte, região, local da sede e selo de acreditação; e, finalmente, Silva et al (2021) indicam, por meio de uma análise de decomposição da variância, que a abrangência nacional, ou regional, e a bandeira da OPS explicou a maior parte das diferenças de rentabilidade.…”
Section: Discussão Dos Resultadosunclassified